El techo de la perfección. Las pinturas del techo del Ateneo de Arturo Mélida - Zozaya-Montes, Maria (2013)
In 1953 the Athenaeum of Madrid was censored, because the Franco dictatorship was afraid it could be masonic. In the common mentalities, it is said that this center has and had masonic reflects, but none has ever proved it scientifically. Here are analyzed the origins of that building and its decorations (1881-1883) and its possible links with the freemasonry. Both are related to the life and works of their author, Arturo Mélida. The results of that material analysis are contrasted here with the -so known as- collective mentalities about the subject.